Self-Reported Body Awareness: Validation of the Postural Awareness Scale and the Multidimensional Assessment of Interoceptive Awareness (Version 2) in a Non-clinical Adult French-Speaking Sample - Da Costa Silva, Lucie; Belrose, Célia; Trousselard, Marion; Rea, Blake; Seery, Elaine; Verdonk, Constance; Duffaud, Anaïs M.; Verdonk, Charles (Frontiers in Psychology, 2022)
Body awareness refers to the individual ability to process signals originating from within the body, which provide a mapping of the body’s internal landscape (interoception) and its relation with space and movement (proprioception). The present study aims to evaluate psychometric properties and validate in French two self-report measures of body awareness: the Postural Awareness Scale (PAS), and the last version of the Multidimensional Assessment of Interoceptive Awareness questionnaire (version 2, MAIA-2). We collected data in a non-clinical, adult sample (N=308; 61% women, mean age 35 ± 12 years) using online survey, and a subset of the original sample (n=122; 62% women, mean age 44 ± 11 years) also completed the retest control. Factor analyses and reliability analyses were conducted. Construct validity of the PAS and the MAIA-2 were examined by testing their association with each other, and with self-report measures of personality (Big Five Inventory), alexithymia (Toronto Alexithymia Scale) and dispositional trait mindfulness (Freiburg Mindfulness Inventory). Factor analyses of the PAS supported the same two-factor structure as previously published versions (in other languages). For the MAIA-2, factor analyses suggested that a six-factor structure, excluding Not-Worrying and Not-Distracting factors, could successfully account for a common general factor of self-reported interoception. We found satisfactory internal consistency, construct validity, and reliability over time for both the PAS and the MAIA-2. Altogether, our findings suggest that the French version of the PAS and the MAIA-2 are reliable self-report tools to assess both components of body awareness (proprioception and interoception dimension, respectively).